Characteristics of dental transposition in digital panoramic radiographs of pediatric patients. Retrospective study - Cuadra Gonzaga, Mayra Katherine (2022)
Objective: To evaluate of characteristics of dental transposition in digital panoramic radiographs of pediatric patients. Methods: A transversal, descriptive and retrospective study was carried out with 2386 digital panoramic radiographs of patients who are among 6 and 17, attended at Cayetano Heredia University dental center from 2015 to 2018. Results: The dental transposition frequency was 0.96%, of which 52.17% were female and the complete dental transpositions were 96.55%. According to the localization in the right-upper quadrant represents 51.72% and left-upper quadrant represents 48.28%. The premolar maxillary canines’ transpositions are most usual and represents 82.76%. Conclusions: The dental transposition frequency was low, the complete dental transposition was more common, and they were located on the upper maxilla with a predilection on the right side. The canine tooth and first premolar transpositions were more usual, and the dental transpositions were predominant on female.